The Influence Of Key Audit Matters (Kams), Audit Committees, And Internal Control Systems On Audit Quality And Its Implications For Fraud Deterrence (Study Of Healthcare Companies Listed On The Indonesia Stock Exchange (Idx) 2019-2023) - Gaol, Yohanes C. E. P. S. L.; Koerniawan, Koenta Adji (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
Every listed company on the Indonesia Stock Exchange (IDX) is required to submit and publish periodic financial reports to the OJK and the public. The fact that financial reports include trustworthy data for decision-making makes them significant. The quality of information can be improved by improving audit quality. Several factors affect audit quality including key audit matters, audit committees, internal control systems, and fraud deterrence. The purpose of this research is to examine how audit quality in health firms is affected by significant audit topics, audit committees, internal control systems, and fraud deterrent within the 2019–2023 timeframe. In this study, a cross-sectional sample of 90 organizations was selected using purposive selection, using a quantitative approach. The SEM-PLS analysis is then used to process the data.